Obstructive sleep apnea and sudden unexpected death in epilepsy in unselected patients with epilepsy: are they associated? - Phabphal, Kanitpong; Koonalintip, Prut; Sithinamsuwan, Pasiri; Wongsritrang, Krongthong; Amornpojnimman, Thanyalak; Ekpitakdamrong, Nichanan; Geater, Alan F. (Sleep & breathing, 2021)
Purpose We aimed to determine (1) the frequency of high-risk sudden unexpected death in epilepsy (SUDEP) in patients with epilepsy who have had obstructive sleep apnea (OSA) in different stages of sleep using the revised SUDEP risk inventory (rSUDEP-7) score instrument and (2) the factors associated with high risk SUDEP in patients with epilepsy who have had OSA. Methods We conducted a cross-sectional study of consecutive subjects who are more than 15 years old without known sleep disorders, recruited from a single epilepsy clinic in a tertiary care facility. Participants underwent polysomnography. Scoring was performed by two blinded board-certified sleep physicians. The relationships between rSUDEP-7 scores and OSA measures were evaluated using Wilcoxon rank-sum test, chi-squared test, and quantile regression. Results Our study population consisted of 95 participants. Overall median (IQR) apnea-hypopnea index (AHI) of our populations was 2.3 (0.7,7.5) events rate per hour; 12 (75%) patients had moderate OSA and 4 (25%) patients had severe OSA. Nine patients had a rSUDEP-7 score of 5 to 7. There was no significant difference between total rSUDEP-7 score or rSUDEP-7 score of > 5 or < 5 and total AHI, supine AHI, non-supine AHI, NREM AHI, or REM AHI; similarly, (2) there was no significant difference in total rSUDEP-7 score between AHI of < 15 or > 15. Conclusion Our study reveals no association between AHI score, OSA, and total rSUDEP-7 score or rSUDEP-7 score of > 5. The pathophysiology underlying SUDEP appears complex. We need further studies on SUDEP to help elucidate the cardiorespiratory mechanisms and predisposing factors.